2021
DOI: 10.7554/elife.66960
|View full text |Cite
|
Sign up to set email alerts
|

Somatostatin interneurons activated by 5-HT2A receptor suppress slow oscillations in medial entorhinal cortex

Abstract: Serotonin (5-HT) is one of the major neuromodulators present in the mammalian brain and has been shown to play a role in multiple physiological processes. The mechanisms by which 5-HT modulates cortical network activity, however, are not yet fully understood. We investigated the effects of 5-HT on slow oscillations (SOs), a synchronized cortical network activity universally present across species. SOs are observed during anesthesia and are considered to be the default cortical activity pattern. We discovered t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 113 publications
(105 reference statements)
2
23
0
Order By: Relevance
“…It seems highly likely that these interneuron classes also have distinct behaviours and roles in the modulation of cortical activity by psychedelics. For example, earlier this year it was reported that a subset of SST entorhinal cortex neurons is strongly activated by their 5-HT2ARs, leading to a profound suppression of population activity by serotonin and serotonin-releasing drugs in vitro and in anaesthetised mice (de Filippo et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It seems highly likely that these interneuron classes also have distinct behaviours and roles in the modulation of cortical activity by psychedelics. For example, earlier this year it was reported that a subset of SST entorhinal cortex neurons is strongly activated by their 5-HT2ARs, leading to a profound suppression of population activity by serotonin and serotonin-releasing drugs in vitro and in anaesthetised mice (de Filippo et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The REBUS model proposes a unifying account of how serotonergic psychedelic compounds affect conscious experience [32]. Serotonergic psychedelics are a specific class of psychoactive compounds including but not limited to lysergic acid diethylamide (LSD), psilocybin, and dimethyltryptamine (DMT), that principally act upon cortical serotonin 2A receptors [54][55][56][57][58][59][60][61][62][63][64] to achieve their profound psychological effects [32,65,66] and therapeutic potential [67][68][69][70][71][72]. Moving forward, we use the term psychedelics to refer to these serotonergic psychedelics.…”
Section: Relaxed Beliefs Under Psychedelics (Rebus)mentioning
confidence: 99%
“…Fast-firing interneurons also provide the sole synaptic communication path between stellate cells, which lack recurrent excitatory connections ( Couey et al, 2013 ; Pastoll et al, 2013 ; but see Fuchs et al, 2016 ). In contrast, a subset of low threshold-spiking interneurons have been shown to suppress network oscillations in mEC ( de Filippo et al, 2021 ). Further, in behaving animals, inhibition from layer 2/3 parvalbumin-positive (Pvalb + ) and somatostatin-positive (Sst + ) interneurons have separate roles in setting the spatial tuning and firing rates of layer 2 grid cells ( Miao et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%